Analysis of Accounting Treatment of Damaged Products for Production Cost Calculation at CV ABC - Ningsih, Nur Afni Fitria; Lasmana, Andy; Hambani, Susy (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The aim of this research is to determine the calculation of the cost of production costs incurred, the accounting treatment of damaged products and the results of analysis after calculating damaged products. The research was conducted at CV ABC Bekasi. The research uses quantitative research methods with a qualitative descriptive method approach. The results for this research are the calculation of the cost of production at CV ABC Bekasi using the Full Costing method. The causes of damaged products at CV ABC Bekasi are exposure to a hot iron and stains that cannot be removed on the product, shadding, wrong unloading and dancing which causes clothes damage and cannot be repaired. The accounting treatment for damaged products at CV ABC Bekasi is normal and salable for sale. CVABC does not include sales proceeds from damaged products into the calculation of the cost of production. The sales proceeds are not charged to factory overhead costs because the company assumes that the proceeds from sales of good products are sufficient to meet the company's profit targets.